The Urban and Architectural Characteristics of Voyvoda Street from Past to Present - Seçmen, Serengül; Makaklı, Elif Süyük (Iconarp International Journal of Architecture and Planning, 2021)
Purpose Voyvoda Street in Galata district of Istanbul originated centuries ago at the inner walls of the medieval city and was one of the most significant of its era, which has preserved its unique character and urban identity. In the nineteenth century, it became an important financial axis for the city. This study aims to understand the factors which determined the axial character of Voyvoda Street and its urban identity. The street, which is under the influence of new dynamics is examined in relation to spatial and functional transformation. Design/Methodology/Approach The analysis was developed by two essential components: the street and the buildings that define the character of the street by its architectural components, and their functional transformation since the nineteenth century. The axial character of the street has been evaluated due to selected criteria. The data is based on literature review, the survey of historical maps, visual materials such as photographs and gravure prints, and on-site observations. Findings The street has been shaped and transformed by social, political, and economic developments, external and internal migrations, the influence of modernist architectural movements, urban reforms, Western innovations in transportation, and technical developments. Voyvoda Street’s strong character as an axis is determined by its historical buildings, which are attached to each other continuously that form a wall defining the boundaries of the street. It is one of the essential pedestrian connections and functions as a path. Since most of the buildings lost their original functions, following the re-use for various needs, the service and cultural industries have become dominant. Although the historical characters of some buildings have been changed by new additions, the original silhouette of the nineteenth century is still dominant.  Research Limitations/Implications Visual materials and resources of some buildings were available in detail, while for some of them, the materials were limited. Originality/Value The previous studies concentrated on urban, and architectural aspects of Galata district as a whole, whereas this study focused on the urban identity of Voyvoda Street. The street and the historical buildings that define the axial character and the image of the street by its architectural components, and their functional transformation have been analyzed.
Keywords: Dönüşüm; Yapılı Miras; Street Identity; Eksenel Karakter; Street identity; NA1-9428; Built heritage; Transformation; Voyvoda street; Axial character; HT165.5-169.9; Built Heritage; Architecture; Voyvoda Street; Sokak Kimliği; Axial Character; City planning